Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve:3m-2(m-3)=1 please help

Sagot :

Answer:

[tex]3m - 2(m - 3) = 1 \\ 3m - 2m - 6 = 1 \\ m - 6 = 1 \\ m = 1 + 6 \\ m = 7[/tex]

PLEASE MARK ME BRAINLIEST

Answer:

m = -5

Step-by-step explanation:

3m-2(m-3)=1

Distribute

3m -2m +6 = 1

Combine like terms

m+6 =1

Subtract 6 from each side

m+6-6 =1-6

m = -5